An Islamic Legal Review of the Joint Liability System Practice in PNM Mekar Financing - Putri ayu Srikandi; Nilfatri; Sri Kadarsih; Reza Okva Marwendi; Alisyah Pitri (Zabags International Journal of Islamic Studies, 2025)
This study examines the implementation of the tanggung renteng (joint liability) system in microfinance practices at PNM Mekaar in Kelurahan Parit Culum 1, from the perspective of Islamic law, particularly the concept of kafalah (guarantee). The research is motivated by the discrepancy between the formal agreement of shared responsibility and the actual practice, where group leaders often bear the burden alone due to other members’ unwillingness to contribute. Using a qualitative case study approach, data were collected through interviews, observation, and documentation involving group members, the group leader, and the PNM branch head. The results show that although the joint liability system aims to promote collective responsibility, it is not fully understood or fairly implemented among members. In several cases, the system shifts the responsibility unfairly onto group leaders, creating moral and financial injustice. From the Islamic legal perspective, while the concept of kafalah allows for such a guarantee mechanism, it must be based on fairness, willingness, and mutual consent. This study contributes to the discourse on aligning microfinance practices with Sharia principles and recommends better socialization, transparency, and regulatory safeguards to uphold justice in group lending schemes.